Mathematical Modeling of Piezoelectric Ceramic Ring Transducers for Functional Instrumentation - К. В. Базіло; В. О. Андрієнко; В. В. Туз; Л. М. Усик; Ю. Ю. Бондаренко (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2023)
The article reviews a mathematical model of piezoelectric ceramic ring transducers which are functional, highly effective, and applicable as components of functional instrumentation devices, such as sensors, automatic control devices, measuring devices, data collection devices, electronic control systems, etc. The main distinctive characteristic of the mathematical model developed in this study is the ability to establish analytical dependencies for determining such electromechanical characteristics of a piezoceramic ring as: electrical impedance, quality factor, elastic modulus, piezo modulus, dielectric constant, as well as the amplitude values of the electric charge and electric current on the electroded surfaces of the piezoceramic ring, thus significantly expanding the range of these products and determine their operational characteristics at the design stage. The key research question of this study is frequency dependence of the change in electrical impedance for a ring made of PZT-type (plumbum zirconate titanate) piezoelectric ceramics, which significantly depends on the values of mechanical and geometric parameters, the wave number of elastic oscillations, as well as the corresponding Bessel and Neumann functions of the first order, according to which a sharp decrease in the electrical impedance from 4900 to 10 Ohms is observed when the quasi-wave number increases from 0 to 2. Also, this study has established a high degree of convergence between the theoretically obtained and experimentally determined electrical impedance modules for ring transducers made of PZT-type piezoelectric ceramics (the discrepancy between the impedance values in these cases did not exceed 16%).